Time series of water samples and stable water isotope measurements collected at Puente Lavalle - Repasch, Marisa N; Scheingross, Joel S; Cook, Kristen L; Sachse, Dirk; Dosch, Sophia; Orfeo, Oscar (In: Repasch, MN et al. (2023): River water chemistry, channel morphometrics, and river incision data for the Rio Bermejo, Argentina [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.959938, 2023)
This dataset contain stable isotope values for water samples collected ~weekly from the Rio Bermejo at the Lavalle bridge (-25.6513, -60.1277) from March 2016 to February 2018. Water samples were filtered to 0.2 micron using a custom filtration device. We measured d2H and d18O on a Picarro L-2140i Cavity Ring-Down Spectrometer at the GFZ Potsdam. Measurements were made in duplicate, normalized to the Vienna Standard Mean Ocean Water (VSMOW), and analytical uncertainty is reported as one standard deviation from the mean. River discharge was measured at the El Colorado gauging station, which is ~100 km down slope from the sampling location.
Keywords: Argentina; channel migration rates; fluvial geomorphology; Foreland basin; river morphometrics; water chemistry